Formulation and characterization of essential oils based antibacterial hand sanitizer gels - Diviyagahage, C.M.; Thuvaragan, S.; Gnanakarunyan, T.J.; Srikaran, R. (Pharmaceutical Society of Sri Lanka, 2021)
Purpose: The usage of herbal-based antibacterial sanitizers is increasing, and they have considerably shown fewer side-effects than sanitizers with synthetic compounds. In the present study, essential oils obtained from cinnamon and lime were used to formulate hand sanitizer gels, and their efficacy was evaluated. Method: Three different hand sanitizer gel formulations were prepared using cinnamon oil (Formulation A), lime oil (Formulation B) and a mixture of cinnamon and lime oil (Formulation C). Carbopol 940 was used as the gelling agent. Tests for organoleptic, physicochemical characteristics and stability were conducted on the prepared formulations. The antibacterial activity of the prepared formulations was evaluated using the agar diffusion method. All three formulations were compared with a commercial liquid hand wash product for their in vitro antibacterial activity. Three-way ANOVA with Tukey's honestly significant difference test was used to compare the antibacterial activity of the hand sanitizer gel formulations. Stability of the three hand sanitizer formulations were assessed. Results: Considerable differences in the pH and viscosity were not observed between the prepared hand sanitizer gel formulations. However, considerable changes in the spreadability were observed between the prepared hand sanitizer gel formulations. A statistically significant difference in antibacterial activity was observed among the three hand sanitizer gels and the commercial hand wash (p<0.05). Formulation C showed the highest antibacterial activity among the prepared hand sanitizer formulations. Based on the stability studies, Formulation A was found to be the most stable. Conclusion: Hand sanitizer gel containing a mixture of cinnamon and lime oils showed the highest antibacterial activity among prepared formulations. However, the most stable formulation was the hand sanitizer gel containing cinnamon oil.
Keywords: Essential oil; Cinnamon oil; Lime oil; Hand sanitizer gel